ASSOCIATION OF VULVAR HYGIENE PRACTICES WITH VAGINAL DISCHARGE IN REPRODUCTIVE-AGE INDONESIAN WOMEN - Meiyana Sinaga; Sarinah Br Silalahi (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2025)
Vaginal discharge is a common reproductive health issue experienced by women of reproductive age. It may be physiological or pathological, and one of the factors influencing the occurrence of pathological discharge is vulvar hygiene practices. Inadequate genital hygiene—such as wearing damp underwear, improper cleansing techniques, or the use of unsuitable cleansing products—can increase the risk of infection and lead to abnormal vaginal discharge. Therefore, proper vulvar hygiene plays an essential role in maintaining women’s reproductive health. This study aims to examine the relationship between vulvar hygiene practices and the incidence of vaginal discharge among women of reproductive age. The research employed a quantitative method with a cross-sectional design. The sample consisted of 19 women of reproductive age selected through a total sampling technique. Data were collected using a questionnaire assessing vulvar hygiene practices and the incidence of vaginal discharge. Data analysis was conducted using the Chi-Square test with a significance level of 0.05. The results showed that nearly half of the respondents demonstrated good vulvar hygiene practices (47.4%), and the majority did not experience vaginal discharge (78.9%). The Chi-Square analysis revealed a significant association between vulvar hygiene practices and the incidence of vaginal discharge, with a p-value of 0.000 (p < 0.05). These findings indicate that better vulvar hygiene practices are associated with a lower risk of developing vaginal discharge. In conclusion, proper vulvar hygiene contributes to the prevention of vaginal discharge among women of reproductive age. Continuous education and health promotion efforts are necessary to enhance women’s knowledge and awareness of the importance of maintaining genital hygiene as a preventive measure against reproductive health problems.